Procedural and Fiscal Customs Facilities in Enhancing the Competitiveness of Indonesia's Manufacturing Industry: A Systematic Literature Review - Suwondo Suwondo; Kadarisman Hidayat; Ari Darmawan (Department of Public Administration, 2026)
Trade facilitation through customs instruments is central to Indonesia's efforts to strengthen manufacturing competitiveness, yet the evidence on how procedural facilities (Authorized Economic Operator/AEO, Mitra Utama Kepabeanan/MITA, the National Logistics Ecosystem/NLE, and the Indonesia National Single Window/INSW) and fiscal facilities (Bonded Zones, Kemudahan Impor Tujuan Ekspor/KITE, and Special Economic Zones) contribute to competitiveness remains fragmented across disciplines and rarely synthesized with methodological transparency. This study conducts a systematic literature review (SLR) guided by the PRISMA 2020 protocol to map, critically appraise, and synthesize the evidence base. Searches were carried out in Google Scholar, DOAJ, ResearchGate, IDEAS/RePEc, and Indonesian institutional repositories using a documented, database-specific search string, with the final search conducted on 15 July 2026. Methodological quality was appraised using the Mixed Methods Appraisal Tool (MMAT 2018). Of 215 records identified, 19 empirical or conceptual studies met the eligibility criteria through the database search, supplemented by 10 additional foundational theoretical and methodological references obtained through backward citation tracking, yielding 29 sources in the final synthesis. The review finds that procedural facilities primarily operate by reducing time, uncertainty, and inspection intensity, while fiscal facilities primarily operate by reducing production costs and improving cash flow; both influence competitiveness indirectly through intermediate variables such as logistics efficiency and supply continuity, moderated by firm size, sector, institutional quality, digital readiness, and regional infrastructure. Evidence on outcomes is mixed rather than uniformly positive, and access to procedural facilities such as AEO and MITA is disproportionately concentrated among large, highly compliant firms, raising equity concerns for SMEs. This review proposes an intermediate-variable conceptual framework (Customs Facilities → Customs and Logistics Efficiency → Firm-Level Outcomes → Manufacturing Competitiveness, moderated by institutional quality, digital readiness, firm size, and sector) and offers a transparent evidentiary basis for future firm-level and sector-specific empirical research.